(3GdHOjY TQM GdJaQjYs - (3GdTGQeSGMis; (3CHh GdbGSe Hf LdGH GdeGdcjs ((3CHh eMeO YHO Gddg Hf eMeO Hf YHO Gddg GdHQcdi s)
(3ChdgG (B:s
(3EPG UGQ GdeMQe eQGQkG dJYOO GdLRGA cJYOO GdcaGQI HJYOO GdEjeGf s
(3BNQgG (B:s
(3ced LejY GdOjhGf GdeSei HGdHOjY ai TQM GdJaQjY s
(3GdfSNI HgG MhGTs
(3YdjgG ebGHdI eDQNI HSfI (B864(3g`s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3Gdabg GdeGdcjs